2014
DOI: 10.2478/bvip-2014-0081
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Brucella sp. and Leptospira sp. in dogs using conventional polymerase chain reaction

Abstract: The study was conducted to detect Brucella sp. and Leptospira sp. in blood samples of dogs in Isfahan and Shahrekord province in Iran. A total of 94 blood samples were collected from dogs of different breed, age, sex, and dogs' type (stray or nonstray). The samples were examined using conventional polymerase chain reaction (PCR). Fourteen (14.89%) dogs were positive for Brucella sp. and 18 (19.15%). dogs for Leptospira sp. There were no significant differences between the prevalence of the pathogens, provinces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Of these, 57.1% (8/14) did not identify any significant factor associated with leptospirosis. Among the studies that observed variables significantly associated with canine leptospirosis, the main risk factors observed were age: older than 4 years (Chou et al ., 2014) and younger than 1 year (Zaidi et al ., 2018), seasonality (Chou et al ., 2014), stray as opposed to a pet dog living in a household (Roach et al ., 2010; Khamesipour et al ., 2014; Paz et al ., 2015), and dogs that lived in urban areas, sharing a common area with human beings and exhibiting a history of contact with rats (Goh et al ., 2019). Detailed information on the risk factor analysis performed in these studies is shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 57.1% (8/14) did not identify any significant factor associated with leptospirosis. Among the studies that observed variables significantly associated with canine leptospirosis, the main risk factors observed were age: older than 4 years (Chou et al ., 2014) and younger than 1 year (Zaidi et al ., 2018), seasonality (Chou et al ., 2014), stray as opposed to a pet dog living in a household (Roach et al ., 2010; Khamesipour et al ., 2014; Paz et al ., 2015), and dogs that lived in urban areas, sharing a common area with human beings and exhibiting a history of contact with rats (Goh et al ., 2019). Detailed information on the risk factor analysis performed in these studies is shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…PCR assay is a specific and sensitive choice for the detection of different bacterial agents [2,22,23]. In this study, 9.…”
Section: Discussionmentioning
confidence: 99%
“…In the only PCR-based study in Iran, 14 out of 94 (14.9%) tested blood samples from companion dogs of Isfahan and Shahrekord cities were reported to be positive by conventional-PCR (32). As the PCR products in the latter study were not confirmed by nucleotide sequencing and the dogs did not show any sign of brucellosis, these results should be taken with caution.…”
Section: Discussionmentioning
confidence: 87%